CAUSATIVE ORGANISMS AND THEIR ANTIBIOTIC SENSITIVITY IN PATIENTS WITH DIFFERENT WAGNER’S GRADES OF DIABETIC FOOT - Safian Ahmed1 , Madiha Shah2 , Muzafar Ali Shaikh3 , Abdul Haque Khan4 , Fiza Shah5 , Sadia Shaikh6 . (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Diabetes mellitus is a modern-day epidemic, with number of people with diabetes having quadrupled in the last three decades. With one in every three people living with pre-diabetes, the prevalence is only expected to rise and together with it, may increase the many complications namely blindness, kidney failure, cardiac arrest, stroke and lower limb amputation. While much effort is dedicated to control of diabetes, it is imperative that meanwhile efforts also be directed at curbing the complications. OBJECTIVE: To determine the frequency, causative organisms and their antibiotic sensitivity in patients with different Wagner’s grades of diabetic foot. METHODOLOGY: This cross-sectional analysis was carried out from August 2018 to January 2019 upon a sample of 60 consenting adult diabetic patients of both genders aged 20 to 70 years (chosen via non-probability, consecutive sampling) having taken no systemic antibiotic therapy for at least the past 48 hours, presenting to the Department of Medicine, at Liaquat University of Medical & Health Sciences, Jamshoro/Hyderabad with diabetic foot infection. The patients were categorized in groups according to Wagner’s classification and their data recorded onto a questionnaire containing inquiries pertaining to their basic bio data, socio-demographic details, disease particulars, infecting micro-organisms and antibiotic sensitivity patterns. The data obtained was analyzed using SPSS v. 21.0. RESULTS: The mean age of the sample stood at 41 years (±9 SD). 62%of the sample comprised of males while the remaining 38% were females. Wagner’s grades in decreasing order of occurrence were grade 3 (36%), grade 2 (28%), grade 4 (20%), grade 1 (10%) and grade 5 (6%). The commonest isolated organisms were Klebsiella pneumoniae, followed by Proteus mirabilis, Staphylococcus aureus, and Escherichia coli. Carbapenems (imipenem and meropenem), Piperacillin and Tazobactam, Amikacin and Vancomycin were among the most effective agents. CONCLUSION: After careful consideration, it can be concluded that Gram Negative organisms were the commonest causative organisms and knowing their sensitivity patterns may help with timely and informed start of appropriate empirical antibiotic therapy.